Theoretical study of collision dynamics of fullerenes on graphenylene and porous graphene membranes - Brandolt, Ricardo [UNESP]; Paupitz, Ricardo [UNESP] (Elsevier, 2020)
A comparative study regarding the behavior of graphene, porous graphene and graphenylene monolayers under high energy impact is reported. Our results were obtained using a computational model constructed to perform investigations of the dynamics of high velocity fullerenes colliding with free standing sheets of those materials. We employed fully reactive molecular dynamics simulations in which the interatomic interactions were described using ReaxFF force field. During the simulations, free standing monolayers of the investigated materials were submitted to collision with a C60 fullerene molecule at impact angles within the range 0°≤θ≤75°. We considered kinetic energies in the range 0eV≤Ek≤1500eV, that corresponds to a projectile velocity v in the range 0Å/fs≤v≤0.2Å/fs. Also, the failure dynamics of each one of the 2-dimensional materials is described in a comparative analysis in which relevant differences and unique features observed in the mechanical stress dissipation processes are highlighted. Finally, performing hundreds of simulations we were able to map many possible scenarios for these collisions and to construct diagrams that elucidate, for each one of the materials, the possible behaviors under the action of a highly energetic C60 projectile as a function of energy and incident angle.
Keywords: Airebo; Collision; Graphene; Graphenylene; Molecular dynamics; Porous graphene; ReaxFF